Dimensione didattica, tecnologica e organizzativa. La costruzione del processo di innovazione a scuola - Limone, Pierpaolo; Pace, Rosaria; Rita Mangione, Giuseppina (Media e tecnologie per la didattica - Open Access, 2016)
The first volume of an editorial project divided into two works: this is dedicated to the relationship between the methodological-didactic, technological and organizational dimensions in the process of school innovation; the second one is dedicated to the inclusive education teachers and the role of technology in the services of skills assessment and career guidance. The aim of both the works is the same: collecting reflections and to support processes of technology adoprtion in educational and training contexts.